Feasibility Analysis of Superior Local Commodity Agroindustry to Increase Farmers' Income Around Forests - Sri Jumiyati (Universitas Muhammadiyah Palu, 2025)
The production of shallots is abundant at certain times, namely during the harvest, causing the price of shallots to be relatively cheap and conversely at a time when shallot production decreases, the price is relatively high. This study aims to find out the non-financial aspects as well as analyze the financial aspects of the local Palu fried onion processing business. The determination of the local fried onion agroindustry in Palu is carried out purposively, while the selection of respondents of business actors/farmers is carried out by census with saturated samples because it involves all members of the group totaling 20 people. The data analysis methods used in this study are qualitative analysis and quantitative analysis. Qualitative analysis was used to find out the general picture of the Palu fried onion agroindustry from non-financial aspects related to business profiles and processing processes which were then described descriptively. Meanwhile, financial analysis is related to Income Analysis, Feasibility Analysis, Break Even Point Analysis and Return on Investment Analysis. The results of the study describe the Organizational Structure and Production Process of local fried onions in Palu. Meanwhile, based on the analysis of financial aspects, it shows that the income of the local fried onion agroindustry in Palu has an income of Rp. 3,540,000 for 1 (one) production, the feasibility value is 1.36. Furthermore, the value of BEP consisting of BEP production of 289 packs and the value of BEP of receipts is Rp. 5,780,000 and a value of 35.54% which means that investment through the local Palu fried onion agroindustry will provide a profit of 35.54%.